The Combined Partial Knockdown of CBS and MPST Genes Induces Inflammation, Impairs Adipocyte Function-Related Gene Expression and Disrupts Protein Persulfidation in Human Adipocytes - Jessica Latorre; Angeles Aroca; José Manuel Fernández-Real; Luis C. Romero; José María Moreno-Navarrete (MDPI AG, 2022)
Recent studies in mice and humans demonstrated the relevance of H2S synthesising enzymes, such as CTH, CBS, and MPST, in the physiology of adipose tissue and the differentiation of preadipocyte into adipocytes. Here, our objective was to investigate the combined role of CTH, CBS, and MPST in the preservation of adipocyte protein persulfidation and adipogenesis. Combined partial CTH, CBS, and MPST gene knockdown was achieved treating fully human adipocytes with siRNAs against these transcripts (siRNA_MIX). Adipocyte protein persulfidation was analyzed using label-free quantitative mass spectrometry coupled with a dimedone-switch method for protein labeling and purification. Proteomic analysis quantified 216 proteins with statistically different levels of persulfidation in KD cells compared to control adipocytes. In fully differentiated adipocytes, CBS and MPST mRNA and protein levels were abundant, while CTH expression was very low. It is noteworthy that siRNA_MIX administration resulted in a significant decrease in CBS and MPST expression, without impacting on CTH. The combined partial knockdown of the CBS and MPST genes resulted in reduced cellular sulfide levels in parallel to decreased expression of relevant genes for adipocyte biology, including adipogenesis, mitochondrial biogenesis, and lipogenesis, but increased proinflammatory- and senescence-related genes. It should be noted that the combined partial knockdown of CBS and MPST genes also led to a significant disruption in the persulfidation pattern of the adipocyte proteins. Although among the less persulfidated proteins, we identified several relevant proteins for adipocyte adipogenesis and function, among the most persulfidated, key mediators of adipocyte inflammation and dysfunction as well as some proteins that might play a positive role in adipogenesis were found. In conclusion, the current study indicates that the combined partial elimination of CBS and MPST (but not CTH) in adipocytes affects the expression of genes related to the maintenance of adipocyte function and promotes inflammation, possibly by altering the pattern of protein persulfidation in these cells, suggesting that these enzymes were required for the functional maintenance of adipocytes.